Combining Ring‐Opening Metathesis Polymerization and Thiol‐Ene Coupling Chemistries: Facile Access to Novel Functional Linear and Nonlinear Macromolecules. Issue 4 (16th January 2014) - Lowe, Andrew B.; Liu, Meina; van Hensbergen, Johannes Arend; Burford, Robert P.; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> The aim of this article is to highlight recent examples in which two powerful synthetic tools, namely ring‐opening metathesis polymerization (ROMP) and thiol‐ene (including the thiol‐Michael variant) click chemistry have been combined to facilitate the preparation of novel functional materials of varying topology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>